Creating Online Learning Experiences - Crosslin, Matt; Benham, Brett; Dellinger, Justin T.; Patterson, Amber; Semingson, Peggy; Spann, Catherine A.; Usman, Brittany; Watkins, Harriet (Open textbook library., 2018)
This book provides an updated look at issues that comprise the online learning experience creation process. As online learning evolves, the lines and distinctions between various classifications of courses has blurred and often vanished. Classic elements of instructional design remain relevant at the same time that newer concepts of learning experience are growing in importance. However, problematic issues new and old still have to be addressed. This handbook explores many of these topics for new and experienced designers alike, whether creating traditional online courses, open learning experiences, or anything in between.